Anthropocentric perspective on climatic variability, potentially toxic elements, and health risk assessment in the Mansehra district: a case study of the Kunhar River, Pakistan. Issue 4 (18th March 2023) - Soomro, Shan-e-hyder; Shi, Xiaotao; Guo, Jiali; Hu, Caihong; Zwain, Haider M.; Jalbani, Shaista; Li, Yinghai; Guo, Yu; Chunyun, Zhu; Gu, Jiahui
Abstract: The quality of the surface water along the Kunhar River in Mansehra district, KPK Pakistan was assessed for ten water samples stations. A variety of parameters indicating water quality including physicochemical parameters, nutrients, heavy metals, and antibiotic residues were measured for both the rainy and dry seasons, the two main tropical seasons in Mansehra, using the standard methods. Kunhar River, one of the local drinking water sources, was studied to assess the heavy metal content, health risk assessment, and its suitability for human consumption. Health risk assessment for all the stations indicated that there is no particularly dangerous single heavy metal, but their cumulative effect is indicated by the hazard index. Concentrations of metals in water have a trend of decreasing in water, indicating that the accumulation of metals can affect the water chemistry of aquatic systems due to any physical or chemical process in the system. Greater consideration should be given to the variety of metals in relationship to multivariate analyses, suggesting that the industrial and residential activities were more important contributors to the pollution of the Kunhar River than the agricultural activities in Mansehra district. Such metals pose risks to aquatic life. HIGHLIGHTS: In the Kunhar River, seasonal fluctuations in the levels of nutrients, toxic substances, as well as certain antibiotics were identified. The study revealed that domestic activities caused significantly more environmental damage to the Kunhar River than agricultural practices. High-pollution sites of the Kunhar River have been affected by human settlement.